2016
DOI: 10.1007/s40753-016-0031-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Level of Engagement with Mathematics Support in Higher Education in Ireland

Abstract: Over the past couple of decades, mathematics support centres have become widespread in higher education, most notably in Ireland, the U.K. and Australia. These centres generally offer a range of free support services to students who feel they need additional help with their mathematics modules. A major large-scale survey of first-year higher education students was undertaken in Ireland to ascertain students' evaluation of mathematics support. There were significant differences in self-reported attendance betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…These findings align with previous research [ 2 4 , 12 ], indicating that student engagement has a second-order structure, with responses to the measurement of engagement grouped through three first-order factors (behavioral, emotional, and cognitive). Moreover, discriminant validity proved that each engagement factor (behavioral, emotional, and cognitive) assesses a different manifestation of engagement; these results align with previous studies [ 2 , 12 , 48 ]. Our findings suggest that focus group work led to the development of items for each engagement factor that effectively capture the attitudes and behaviors that reflect school engagement in college students.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings align with previous research [ 2 4 , 12 ], indicating that student engagement has a second-order structure, with responses to the measurement of engagement grouped through three first-order factors (behavioral, emotional, and cognitive). Moreover, discriminant validity proved that each engagement factor (behavioral, emotional, and cognitive) assesses a different manifestation of engagement; these results align with previous studies [ 2 , 12 , 48 ]. Our findings suggest that focus group work led to the development of items for each engagement factor that effectively capture the attitudes and behaviors that reflect school engagement in college students.…”
Section: Discussionsupporting
confidence: 90%
“…Given that both factor loadings and interceptors resulted in invariance, we examined the latent mean differences in second-order factors (behavioral, emotional, and cognitive engagement). As other scholars [2,12,48] reported, our results from mean scores indicate that females have higher levels of behavioral engagement than males. Consistent with previous research [49], we found no significant differences between males and females regarding emotional and cognitive engagement.…”
Section: Measurement Invariance By Gendersupporting
confidence: 80%
See 1 more Smart Citation